Associated Psychological Disorders and Impairment of Emotional Regulation among Patients with Multiple Sclerosis - M. T. Andreeva; T. A. Karavaeva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The review of data  from  the  available literature  cites the  results of studies of psychological disorders  comorbid  to  multiple  sclerosis and  highlights  scientific papers  detailing  domestic  and  foreign research. The high prevalence of affective and adaptive impairment  is linked both to the neurophysiological particularities of this chronic, progressive, neurodegenerative illness and to psychological factors — individual personality traits and the attitude of those afflicted to their illness, to the change in their social functioning and  to  their  prognosis. It  is demonstrated  that  patients  with multiple  sclerosis have a significantly higher frequency of depressive and anxiety disorders than  the general population,  which suggests the need for an integrated, personalized approach to people with this illness.